WIREFRAME WEBSITE INTERFACE DESIGN MIFTAHUL HUDA MOSQUE PROSPERITY COUNCIL USING THE DESIGN THINKING METHOD - Santi Purwanti; Jaja Jaja; Rakhmayudhi Rakhmayudhi; Dian Perdiansyah; Sahrul Ramdan (SEAN Institute, 2022)
The website is a necessity in disseminating information that can be accessed through cross platforms and makes it easy for users to access the information they need. The Mitahul Huda Mosque Prosperity Council (DKM) has problems in terms of disseminating information which has a wider scope, to solve existing problems it is necessary to make a website, but in making a website it is necessary to pay attention to the aesthetics and suitability of the function of the display to be designed so that users feel more comfortable and feel that they always want to access information on the website, based on this, it is necessary to make an interface design that suits the needs of users by using the Design Thinking method. Design Thinking has five stages and three stages that will be used to design the Miftahu Huda Mosque Prosperity Council (DKM) website interface. In making the interface design the tool used is figma so that it makes it easy for the team to create interface designs simultaneously and communicate through visuals. From this research, wireframes were generated for home, articles, services, galleries, about, contacts and search